Secure file sharing system with strong password and one time password authentication / Chee Lee Chong and Nur Ziadah Harun - Chee, Lee Chong; Harun, Nur Ziadah (UiTM Cawangan Perlis, 2025)
A file-sharing system is a system that allows users to share their files with other users. In the digital age, file-sharing systems have become integral for various sectors, including corporate, educational, and creative fields. Inadequate security measures in file-sharing systems have become a significant concern. Many current systems expose users to unauthorized access and data breaches due to weak authentication methods, such as using simple username and password combinations. Additionally, the lack of a secure password when files are shared through links exacerbates the risk, as unauthorized users can access confidential data without needing a password. This paper presents the development of a secure file-sharing system incorporating strong password protocols and one-time password (OTP) authentication to address vulnerabilities in existing systems. The proposed system ensures robust security by implementing multi-factor authentication, end-to-end encryption, hashing in database and secure session management. The users must provide a strong password and OTP for login, register and reset password process. Key features include user management and comprehensive file management functionalities. The system offers user account management, space management, and user file management, ensuring that administrative controls are in place to manage user activities and storage efficiently. The developed system implements the file management module such as upload, download, rename, move, create folders, and share with password protection. The implementation details and testing results confirm the system's effectiveness in providing a secure and user-friendly file-sharing platform. At the end of this project, the proposed system has achieved the objective of developing a file-sharing system that can share files securely.